Efektivitas Penggunaan Gigi Tiruan Sebagian Lepasan terhadap Fungsi Pengunyahan pada Masyarakat Desa Pinasungkulan Kecamatan Modoinding - Mangundap, Gledis C. M.; Wowor, Vonny N. S.; Mintjelungan, Christy N. (e-GiGi, 2019)
Abstract: Removable partial denture is indicated to patients who lose some of their original teeth. The use of denture plays an important role in the recovery of masticatory system lost or disturbed due to tooth loss. This study was aimed to obtain the effectiveness of the use of removable partial dentures on the function of mastication. This was a quasi experimental study with one group pre and post test design. Population consisted of the community using removable dentures at Desa Pinasungkulan Modoinding, based on the prevalence of 879 denture users. There were 16 denture users as samples obtained by using purposive sampling method. We used questionnaire that had been tested for validity and reliability and the Wilcoxon test for data analysis. The results showed that the score of the effectiveness of mastication without using dentures was 207, categorized as 'less effective', meanwhile, the score of with using denture was 293, categorized as 'effective'. The Wilcoxon test resulted in a p-value of 0.004 which meant that there was a difference in masticatory function between using denture and without using denture. In conclusion, the use of removable partial denture was effective on the masticatory function of the community at Desa Pinasungkulan, Modoinding.Keywords: partial removable denture, effectiveness of mastication Abstrak: Gigi tiruan sebagian lepasan (GTSL) diindikasikan pada pasien yang kehilangan sebagian gigi aslinya. Penggunaan gigi tiruan berperan penting dalam pemulihan sistem pengunyahan yang hilang atau terganggu akibat kehilangan gigi. Penelitian ini bertujuan untuk mengetahui efektivitas penggunaan GTSL terhadap fungsi pengunyahan. Jenis penelitian ialah quasi eksperimental dengan one group pre and post test design. Populasi penelitian yakni masyarakat pengguna GTSL di Desa Pinasungkulan Kecamatan Modoinding yang dihitung berdasarkan prevalensi pengguna gigi tiruan sebanyak 879, dengan besar sampel 16 pengguna GTSL diperoleh dengan menggunakan metode purposive sampling. Instrumen penelitian berupa kuesioner yang telah dilakukan uji validitas dan reabilitas. Analisis hasil penelitian menggunakan uji statistik Wilcoxon. Hasil penelitian mendapatkan skor pengukuran efektivitas pengunyahan tanpa memakai GTSL sebesar 207 (kategori ‘kurang efektif’) sedangkan setelah pemakaian GTSL perolehan skor sebesar 293 (kategori ’efektif’). Hasil uji Wilcoxon mendapatkan nilai p=0,004, yang berarti terdapat perbedaan fungsi pengunyahan tanpa menggunakan GTSL dan setelah menggunakan GTSL. Simpulan penelitian ini ialah penggunaan GTSL efektif terhadap fungsi pengunyahan pada masyarakat Desa Pinasungkulan Kecamatan ModoindingKata kunci: gigi tiruan sebagian lepasan, efektivitas pengunyahan